Judicial review of technical decisions: the EU damages directive in the context of italian law - Vese, Donato (P.A. Persona e Amministrazione, 2023)
The main argument of this paper is that the Italian legal system does not – in its current form – allow adequate judicial review of technical decisions. Yet, taking seriously the interpretation of Article 6, paragraph 1 of the European Convention on Human Rights and Article 24 of the Italian Constitution as key norms establishing the right to a fair trial and the right to a defence as its starting point, I suggest that such legal orders can provide better protection for individuals through a theoretical paradigm shift rather than through positive law.